Pendampingan dan Penguatan Peternak Lebah Madu Trigona dalam Memanfaatkan Digital Marketing (Shopee) Desa Parappe Kabupaten Polewali Mandar - Mukhram, Muhammad; Ayuandiani, Wulan; B, Indayani; Nurhasan, Muhammad Taufiq (MOVE: Journal of Community Service and Engagement, 2025)
Parappe Village is an area with significant ecological and economic potential in the development of stingless bee (Trigona) commodities. However, this potential has not been optimally supported due to limited production capacity and relatively small sales volume, as the market share is still local. The purpose of this activity is to provide guidance and training on creating store management accounts and content creation so that beekeepers can take advantage of a wider market, especially the Shopee marketplace, thereby increasing their production and sales volume. As a result of this activity, beekeepers better understand the importance of marketing their products on the Shopee marketplace and gain a larger market share. As a result, in a short period, they were able to secure their first buyer on the marketplace, and their product already has strong competitiveness due to its attractive packaging and nutritional information label issued by the Ministry of Health. Successfully utilizing the marketplace will increase sales volume and encourage the community in Parappe village to focus on being trigona honey bee farmers and also to use Shopee marketplace as a marketing platform.